Eu sou nós: a cidadania comunicativa intercultural nas inter-relações das pessoas comunicantes com o filme Residente - Rodrigues, Raiana da Silva (Universidade do Vale do Rio dos Sinos, 2021)
This investigative adventure is about communicative interrelationships. I pick up my spyglass and other necessary tools for the trip with a focus - the interrelationships of people communicating with the film Residente. On this journey, I seek to discover whether these relationships make it possible to reflect and recognize identity differences in order to contribute to the construction of an intercultural communicative citizenship. In order to understand the surroundings of the problem, I make a movement of contextualization around the object of reference, seeking and mapping the proceduralities and appropriations that involve it. To support the findings, I call on the author / s dialogues that give account of the theoretical-methodological contributions and the people who participated in the interviews. To deal with this journey and its challenge, I guide its epistemic dimension, through transmethodology, which guided all the processes and methodological arrangements carried out. To think about the investigated communication processes, I try to nurture myself from perspectives to think about mediatization, cultural identities, communicating people and intercultural communicative citizenship. In empirical research, I carry out an exploratory phase, based on questionnaires made available in digital environments, to support the choices of people who participate in the systematic phase of the research. In this phase, which had eight participants, I conduct in-depth interviews and dynamics to map the images / narratives of the film relevant to these interviewees. From the dialogues of who these people are and how they perceive and understand the world, it was possible to observe that the film contains elements that collaborate to show the cultural realities that have long been denied, misunderstood and excluded and to broaden the understanding of people about the multiplicity and plurality of cultural identities for the construction of an intercultural communicative citizenship.
Keywords: Filme Residente; Cidadania comunicativa intercultural; Identidades culturais; Pessoas comunicantes; Mediações culturais; Resident movie; Intercultural communicative citizenship; Cultural identities; Communicating people; Cultural mediations; ACCNPQ::Ciências Sociais Aplicadas::Comunicação